2022
DOI: 10.18632/aging.203824
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin suppresses NLRP3 inflammasome activation in intracerebral hemorrhage via TLR4- and MyD88-dependent pathways

Abstract: Intracerebral hemorrhage (ICH) is a common neurological condition that causes severe disability and even death. Even though the mechanism is not clear, increasing evidence shows the efficacy of atorvastatin on treating ICH. In this study, we examined the impact of atorvastatin on the NOD-like receptor protein 3 (NLRP3) inflammasome and inflammatory pathways following ICH. Mouse models of ICH were established by collagenase injection in adult C57BL/6 mice. IHC mice received atorvastatin treatment 2 h after hema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…NLRP3 inflammasome-mediated pyroptosis has been thought to be an important trigger of neutrophil airway inflammation in asthma [ 36 38 ]. Previous studies have reported that TLR4 can promote NF-κB activation by interacting with the adapter molecule MyD88, induce NLRP3 inflammasome and caspase-1 activation, and trigger pyroptosis [ 39 41 ]. Concurrently, the negative regulatory effect of MUC1 on the TLR4/MyD88/NF-κB pathway has been described in other diseases, such as acute lung injury and acute kidney injury [ 26 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…NLRP3 inflammasome-mediated pyroptosis has been thought to be an important trigger of neutrophil airway inflammation in asthma [ 36 38 ]. Previous studies have reported that TLR4 can promote NF-κB activation by interacting with the adapter molecule MyD88, induce NLRP3 inflammasome and caspase-1 activation, and trigger pyroptosis [ 39 41 ]. Concurrently, the negative regulatory effect of MUC1 on the TLR4/MyD88/NF-κB pathway has been described in other diseases, such as acute lung injury and acute kidney injury [ 26 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Constipation caused by decreased intestinal motility is one of the common clinical manifestations of ALS [ 85 ]. Intestinal motility is mainly regulated by ANS and ENS [ 79 ].…”
Section: Brain-gut-microbiota Axismentioning
confidence: 99%
“…Activation of NLRP3 inflammasome can regulate caspase-1-dependent pathways and the release of pro-inflammatory cytokines such as IL-1β to respond to cell stress and infection. However, persistent neuroinflammation and brain injury will occur when NLRP3 inflammasome is over-activated [ 85 ], therefore aggravate the symptoms of the disease.…”
Section: Brain-gut-microbiota Axismentioning
confidence: 99%
“…Statins, also known as 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase inhibitors, are a class of cholesterol-lowering medications that also possess cardiovascular protective effects [93]. Atorvastatin, which shows efficacy in attenuating chronic IH-induced myocardial and neural inflammation via suppressing TLR4/MyD88/NF-κB signaling pathways [33,40,94], also suppresses NLRP3 inflammasome activation [95], although this has not been tested in IH models. A recent clinical trial indicates promising protective effects of atorvastatin against cardiovascular risks in OSA patients [96].…”
Section: Mirna/nlrp3 Signalingmentioning
confidence: 99%